Utilization Of Midwives As Health Workers of Public Health Center In Implementing The Policy Of Nutrition Improvement Efforts For Balita at Central Buton Regency of Southeast Sulawesi Province - Asfira Sugiarto; Ch. Retnaningsih; Yovita Indrayati (SOEPRA, 2018)
To utilize midwives as health workers was essential in rural communities sinceone of midwife’s duties was to carry out the care of balita (children under five). Themidwives had direct contact with the balita’s mothers, from pre‐natal phase to postnatal.They could be utilized to overcome malnutrition problems through thegovernment’s policy in accordance with the Article 26 paragraph (2) of the Act Nr. 36 of2009 on Health Affairs. This study applied socio‐legal studies approach using primary andsecondary data. The data gathering was conducted by having interviews with somesources and respondents beside having library and related documents studies. This studywas analytical‐descriptively written. The results showed that the Government of CentralButon Regency had not had a special regulation in relation with utilizing midwives toimplement the policy of nutrition improvement efforts. Nevertheless, the government ofCentral Buton Regency remained using the basic legal products that had been previouslyissued, namely Local Regulation of Central Buton Regency Nr. 12 of 2016 on Formation andComposition of Regional Devices of Central Buton Regency and Central Buton Regent’sRegulation Nr. 38 of 2016 regarding Position, Organizational Structure, Duties andFunctions and Administration of Health Office of Central Buton Regency. The healthworkers at the Wamolo, Rahia and Lakudo Public Health Centers (Puskesmas)experienced several obstacles in implementing nutrition improvement efforts for balitas,namely, among others, lack of budget provided by the local government (APBD),particularly the budget for nutrition, lack of midwives as the human resources andnutrition, inadequate health facilities and the existing roads that remained rocky andhard to travel.